Football team, California Polytechnic, 1915 (1915)
Group photo of football team on the field. Players wearing pads and are holding footballs. Names on back: (Back Row) Martin Martinsen, Frank Ornantia, Tildo Tomassini, Willie Green, David Fell, Arthur Scarlett, John Brown, Orvin Harvey, Chester Whaley, Perry, Martinsen. (First Row) Bud Muzio, Fergus, Arthur Matthews, Arthur Trussler [?], George Difam [?], Frank Kellogg, Marton R. Herr, Mick Gates, Lenord Sebastian. (Front) Baldwin Cheda [?].